2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26477
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Dimensional Typology for Characterizing Student Peer and Instructor Feedback in Capstone Design Project Courses

Abstract: Ada Hurst is a Lecturer in the Department of Management Sciences at the University of Waterloo. She has taught and coordinated the capstone design project course for the Management Engineering program since 2011. She also teaches courses in organizational behavior, theory, and technology. She received a Bachelor of Applied Science in Electrical Engineering, followed by Master of Applied Science and Doctor of Philosophy degrees in Management Sciences, all from the University of Waterloo. Ada's research and teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the module, students are first exposed to a short presentation on the value and potential benefits of engaging in feedback for self-development, team functionality and as an important skillset for professional work. They are then introduced to a framework that encourages progression through three key feedback stages: interpretation (clarifying questions to expand understanding beyond what has been presented), evaluation (assessment of what has been presented), and recommendation (further information and ideas about what can be done to progress the design) [5]. Preliminary research suggests that students are either unable to move past clarification questions, or they move right to making recommendations, neglecting to take the time to fully understand the problem.…”
Section: Module 4 -Reinforcing Communication and Team Membership Skillsmentioning
confidence: 99%
“…In the module, students are first exposed to a short presentation on the value and potential benefits of engaging in feedback for self-development, team functionality and as an important skillset for professional work. They are then introduced to a framework that encourages progression through three key feedback stages: interpretation (clarifying questions to expand understanding beyond what has been presented), evaluation (assessment of what has been presented), and recommendation (further information and ideas about what can be done to progress the design) [5]. Preliminary research suggests that students are either unable to move past clarification questions, or they move right to making recommendations, neglecting to take the time to fully understand the problem.…”
Section: Module 4 -Reinforcing Communication and Team Membership Skillsmentioning
confidence: 99%
“…In the post-assessment, the Collaborate quadrant was similar to the Compete quadrant. While this mechanical engineering capstone design experience focuses on creative problem solving and the design of a novel product, aligning with typical capstone outcomes [9,30], the Create quadrant post-assessment score was lower than each of the other quadrants. Table 3 summarizes expectations and results for the full study sample.…”
Section: Analysis Of Full Study Samplementioning
confidence: 95%
“…Increased focus on engineering leadership development creates the need to assess outcomes related to leadership in the university setting. While assessing professional skills can be challenging, engineering programs have been doing it for years for outcomes such as teamwork and communication [7][8] [9]. Engineering programs often rely on capstone design courses to address many of the ABET Criterion 3 outcomes [10], and these courses also provide an opportunity for faculty to assess leadership development.…”
Section: Introductionmentioning
confidence: 99%
“…From an educational or learning standpoint, providing a framework or categorization when learning new concepts can support the development of the associated skills. When it comes to the categorization of feedback, Hurst and Nespoli [4] encourage conscious consideration of the following three types: interpretation/comprehension, evaluation, and recommendation. Studies have shown that, while instructors are able to provide balanced feedback that seeks to comprehend the design, provide an assessment, and suggest improvements, students are typically not comfortable providing evaluation-or recommendation-type feedback to their peers.…”
Section: Importance Of Feedbackmentioning
confidence: 99%
“…Next, the facilitator introduces a feedback model to help support the development of feedback skills. The model encourages progression through the three types of feedback identified by Hurst and Nespoli [4]. According to the model, the first feedback stage is interpretation, where the feedback-giver summarizes or paraphrases to check understanding, as well as asks questions to clarify information and to expand their understanding beyond what has been presented.…”
Section: Workhop Introductionmentioning
confidence: 99%